MANIFESTATION OF INNER PEACE VALUES INDONESIAN TEXTBOOKS: RELEVANCE AND IMPLICATIONS ON THE DEVELOPMENT OF PEACE-BASED TEXTBOOKS - Risaldi, Dedi; Pratiwi, Yuni; Andajani, Kusubakti (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
This study aims to determine the values of peace contained in Indonesian language textbooks and the relevance and implications for the development of peace-based textbooks. The method used is a qualitative research method with an analytical descriptive approach. The data used is in the form of words, pictures and not in the form of a collection of numbers. The data source for this research is the Indonesian language textbooks of the independent curriculum. Data collection technique is library technique. Fund analysis was carried out using the method of content analysis or content analysis. The results of the study show that there are four values of peace contained in the Indonesian language textbooks of the independence curriculum. The four values are the value of self-acceptance, the value of not being prejudiced, the value of understanding conflict, and the value of diversity. Relevance and implications for the development of textbooks are needed to support learning and provide knowledge from an early age about the Indonesian language and ways to solve peace problems.